Father’s and Son’s Courage in Cormac McCarthy’s The Road (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
Father’s and Son’s Courage in Cormac McCarthy’s The Road Mohammand Faiz, Sastra Inggris, Fakultas Bahasa dan Seni, UNESA Prof. Dr. FD Kurnia, M.Pd., Sastra Inggris, Fakultas Bahasa dan Seni, UNESA Abstrak Life is the gift that the God gives the human, where there are many challenges and problem that the human have to face in it. In doing the life human needs courage in order to be able to handle every challenges and problems that comes to them. There are many kinds of problem in the life; family, social, economy, or even disaster that can destroy the earth such as described in Cormac McCarthy’s The Road where the environment is devastated because of disaster and earthquake. This devastation causes great damage and also makes many creatures dead. It surely makes people who live in the devastation of earth find difficulty in doing the life because of little food, supplies and also the air is unclean because it is filled by ash and dust, especially the main character the father and the son. It forces them to struggle for survival and to stay alive. They have to keep trying to find food, water or place to survive. There for, there are some problems about how the courage describes in the novel, which are delivered to two main questions of (1) How is father’s and son’s courage in Cormac McCarthy’s The Road? And (2) How is the impact of their courage to themselves? In analyzing the problems, the writer uses psychoanalysis theory by Sigmund Freud to know how the courage happens to the main character and also the theory of courage including its types. To get a clear analysis, this research uses descriptive quality method. It means the quality of data becomes the reference of the work rather than the quantity of the data. So, it is clearly seen how their courage is in struggling to survive from the ruined world. They have to undergo the hard life; hard to breathe, hard to find food and they are always hunted by the fear of the devastation of earth’s threaten. And with the courage, they can survive and stay alive because the courage has given strong stance, confidentiality, faith, spirit and power to struggle for survival from the devastation of earth. Keywords: Psychoanalysis, courage, physical courage, moral courage. Abstrak Hidup adalah hadiah yang tuhan berikan kepada manusia yang mana di dalamnya terdapat banyak tantangan dan masalah yang harus dihadapi. Dalam menjalani kehidupan manusia membutuhkan keberania agar bisa menghadapi tantangan dan masalah yang datang. Ada banyak macam permasalahn yang ada dalam kehidupan; masalah keluarga, sosial, ekonomi atau bahkan bencana yang bisa menghancurkan bumi seperti yang terjadi dalam novel The Road karya Cormac McCarthy yang digambarkan seluruh lingkungan musnah karena bencana dan gempa bumi. Kehancuran tersebut menyebabkan kerusakan yang luar biasa dan juga menyebabkan banyak makhluk hidup yang mati. Hal itu tentunya membuat orang-orang yang hidup dalam kehancuran bumi tersebut merasa kesulitan dalam menjalani kehidupan karena persediaan makanan yang sedikit dan juga udara yang tidak bersih karena abu dan debu, terutama tokoh utama, ayah dan anak. Hal itu memaksa mereka untuk berjuang bertahan hidup. Mereka harus tetap mencoba untuk bisa mtempatendapatkan makanan, air dan tempat untuk berlindung. Oleh karena itu, ada beberapa masalah tentang bagimana keberanian digambarkan dalam novel tersebut, yang kemudian memunculkan dua dasar pertanyaan (1) Bagaimana keberanian ayah dan anak digambarkan dalam novel The Road karya Cormac McCarthy? dan (2) Bagaimana dampak keberanian bagi diri mereka sendiri. Dalam menganalisis permasalahan tersebut, penulis menggunakan teori psikoanalisis oleh Sigmund Freud untuk mengetahui keberanian yang terjadi pada tokoh utama, dan juga menggunakan teori keberanian dan tipe-tipenya. Untuk mendapatkan analisis yang jelas, skripsi ini menggunakan metode descriptive quality dimana kualitas data menjadi poin utama daripada jumlah data. Jadi, terlihat jelas bagaimana keberanian mereka dalam berjuang untuk bertahan hidup dalam kerusakan dunia. Mereka harus menjalani kehidupan yang sulit; sulit bernafas, sulit mendapatkan makanan dan mereka juga selalu dihantui oleh rasa takut akan ancaman-ancaman dari kehancuran bumi. Dan dengan keberanian, mereka bisa bertahan hidup, karean keberanian tersebut telah memberikan pendirian yang kuat, kepercayaan diri, semangat dan kekuatan untuk bertahan hidup dari kehancuran bumi. Kata kunci: Psikoanalisis, keberanian, keberanian fisik, keberanian moral. introduction Everybody must have ever heard of courage, but some of them do not know what the courage is. According to the Advanced American Dictionary, courage is a “quality of mind or spirit that enables one to face danger, fear, or vicissitudes with self-possession, confidence, and resolution.” This all suggests that the quality of courage allows the human being to face life, especially in the moments where someone can experience fear or danger. Courage is so important for people, because with courage people will have a strong stance for doing something. Samuel Johnson said “Courage is the greatest of all the virtues, because if you haven't courage, you may not have an opportunity to use any of the others” (Raymond E. Beckham, 2006: 91). Courage is indeed very important thing, and people must have bravery or courage because it can influence the success of people. Everything will lose without courage. Life is the most beautiful gift the God has given the human. Samuel Butler said in Vincent Vinci that Life is the art of drawing sufficient conclusions from insufficient premises (2000:64). But, life is not as easy as spoken, because life offers everything for people. There are many problems the people must face, and the problems are also varied. There are trivial problems and also complicated that it is difficult to solve and it certainly needs courage to confront them. The novel entitled “The Road” is a novel that adapts the topic of courage and strength. This novel is created by Cormac McCarthy. Cormac McCarthy is an American writer. He finished in writing The Road in 2006. The Road is Cormac McCarthy's most recent novel, describes the bleak journey of a father and son across a post-apocalyptic American landscape. He was visiting El Paso, Texas, with one of his sons, John Francis McCarthy, in 2003 when the initial idea for The Road was born: McCarthy envisioned how the city would look in the future. McCarthy dedicated this novel to John. This novel describes the hardship of two people, father and son, who struggles to survive in the devastation of earth. The author shows the courage when he takes you on a journey of them through a ravaged landscape through their heartfelt story. They struggle to survive in the harsh weather with little food, supplies, or shelter. The story describes the journey south after an unnamed catastrophe that struck the world. The man and the boy, who also remain unnamed throughout the entire novel, travel through the rough terrain of the southeastern United States. The conditions they face are unforgiving: rotted corpses, landscapes devastated by fire, abandoned towns and houses. These two travelers are among the few living creatures remaining on earth that have not been driven to murder, rape, and cannibalism. This article has two related research goals that will be discussed and explained. The first is to describe father’s and son’s courage in Cormac McCarthy’s The Road. The writer will give a describing how the father’s and son’s courage in the novel. The second is to reveal the impact of father’s and son’s courage to themselves in Cormac McCharty’s The Road. This article will give the information about the impact of their courage to themselves. “The Road” is a great novel. McCarthy does a wonderful job at the beginning to bring you into the story. He provides you with immense detail to paint a gray and mystic scene. He continuously provides details of the surroundings to keep you interested. Complementing the immense detail is an extraordinary story line. Not only that, but the novel has also met with great critical success. In 2006, McCarthy was awarded the James Tait Black Memorial Prize in fiction, the Believer Book Award and was a finalist for the National Book Critics Circle Award for fiction. On April 16, 2007, the novel was awarded the 2007 Pulitzer Prize for fiction. In 2012, it was shortlisted for the Best of the James Tait Black. McCarthy's literary repertoire includes revisions of various genres, including the crime thriller (No Country for Old Men) and the Western (the Border Trilogy). Some readers entertain an ongoing debate regarding whether The Road should be classified as fiction, science fiction, or even horror, given McCarthy's brutal prose and unflinchingly vivid vision of what could be considered a hell on earth. Nonetheless, most people agree that The Road is a deeply moving, if also deeply disturbing, work of unparalleled literary genius that transcends any discussion of genre. In analyzing the novel, the article uses psychoanalysis theory. It is because the topic is about psychology. Psychoanalysis is a method of investigating and treating personality disorders and is used in psychotherapy. According to Ernest Van Den Haag, Psychoanalysis refers to Freud techniques of investigation which he was led by the use of his method, and finally to a treatment of personality disorders which uses the method and the theory. (1963: 24). The psychoanalysis that is used is Sigmund Freud theory. They are Id, Ego and Super-ego. Frank Tallis (2002: 61). The first and the oldest agency of the apparatus is called the id, where the instincts come from and to every living creature. Id contains the demand of basic biological needs of life; food, sleep, sex, and more. It is the only component of personality that is present from birth. It operates unconsciously, and its principle function is to bias mental life in such a way as to engineer the discharge of libido. The ego has conscious, preconscious and unconscious. It has a largely managerial function in initiating and monitoring thought and movements. He also said that the ego develops from the id and ensures that the impulses of the id can be expressed in a manner acceptable in the real world. So, the ego deals with the reality. After the id and the ego, there is a third power which the ego must take in the consideration. It is called super-ego; parental and external influences to the ego. The development of the super-ego occurs in the long period of childhood during the influences of the parents and continue along contributions come from others. In an action, the ego must satisfy the id and the super-ego and also aware of the external condition and reality. Super ego is the aspect of personality that holds all of the internalized moral standards and ideals that acquire from both parents and society. It refers to the sense of right and wrong. The superego also has conscious, preconscious and unconscious regions. But the function is to act as moral judge or making judgments. The article is also used the theory of courage and its type. According to Gelven in Mufid James Hannush (2002: 107) “courage is the ability to endure the tension between the opposing forces of attraction or repulsion. . . what repels is the fear of pain, what attracts is the lure of significance and wholeness”. From the theory above can be concluded that courage allows a person to engage life’s challenges and problems, stresses and storms, in spite the fears, weaknesses, and imperfections, without losing the existential worth. Commonly, courage is divided into two different types. They are physical courage and moral courage (Jerry A. Webster, 2012: 64). Daniel A. Putman said that physical courage is the ability to overcome a fear of death or physical harm (2004: 1). From the definition, it can be concluded that physical courage has two components. They are fear of death (Thanatophobia) and physical harm. Fear of death or it is known as Thanatophobia is one of the most universal fears, and maybe the basis of phobias. The term